2008
DOI: 10.1038/onc.2008.118
|View full text |Cite
|
Sign up to set email alerts
|

Snai1 and Snai2 collaborate on tumor growth and metastasis properties of mouse skin carcinoma cell lines

Abstract: Snai1 (Snail) and Snai2 (Slug), the two main members of Snail family factors, are important mediators of epithelial-mesenchymal transitions and involved in tumor progression. We recently reported that Snai1 plays a major role in tumor growth, invasion and metastasis, but the contribution of Snai2 to tumorigenesis is not yet well understood. To approach this question we have silenced Snai2 and/or Snai1 by stable RNA interference in two independent mouse skin carcinoma (HaCa4 and CarB) cell lines. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
74
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 33 publications
12
74
1
1
Order By: Relevance
“…It was previously demonstrated that Snail knockdown in the squamous carcinoma HaCa4 cell line has a large effect on cellular invasiveness, tumour growth and metastasis. 28 In contrast to BCC, SCC can metastasise in humans. Indeed, in mice with primary SCCs we identified metastatic lung nodules displaying distinct features of skin differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that Snail knockdown in the squamous carcinoma HaCa4 cell line has a large effect on cellular invasiveness, tumour growth and metastasis. 28 In contrast to BCC, SCC can metastasise in humans. Indeed, in mice with primary SCCs we identified metastatic lung nodules displaying distinct features of skin differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…30) SLUG also induced the expression of some mesenchymal genes, fibronectin. 31) Thus the identification of SLUG as a novel target of ROCK is relevant to understanding EMT mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 EMT in development and possibly in cancer progression can be mediated by a group of transcription factors (ie, Snail, Slug, and Twist) that, when activated, induce phenotypic changes in cell behavior. 19,20,45,46 These changes involve a loss of polarity and loosening of tight cell-cell junctions, coinciding with decreased levels of functional epithelial markers, especially E-cadherin. A gain of mesenchymal characteristics is also observed, including increased motility and expression of mesenchymal markers (N-cadherin, vimentin, fibronectin).…”
Section: Discussionmentioning
confidence: 99%